Human liver glucokinase gene: cloning and sequence determination of two alternatively spliced cDNAs. - Tanizawa, Y (1991)
A human liver glucokinase (ATP:D-hexose 6-phosphotransferase, EC 2.7.1.1) cDNA was isolated from a liver cDNA library. This cDNA (hLGLK1) appeared to be full length [2548 base pairs (bp) plus additional poly(A) residues], as its size was consistent with a single 2.8-kilobase (kb) glucokinase mRNA on Northern blot analysis of liver poly(A)+ RNA. The cDNA contained an open reading frame of 1392 bp that predicted a protein of 464 amino acids and a molecular mass of 52 kDa; this protein has 97% identity to rat liver glucokinase. Fourteen residues on the amino terminus of the predicted human liver glucokinase, however, differed completely from those of the predicted rat liver enzyme and could be explained by alternative splicing of a 124-bp cassette exon in human cDNA. A second glucokinase cDNA (hLGLK2), missing the 124-bp cassette exon, was isolated by PCR amplification of human liver cDNA. The hLGLK2 cDNA contained an open reading frame of 1398 bp from an ATG codon at position 164, encoding a predicted protein of 466 residues, 98% identical to the rat enzyme, but different from the predicted protein of hLGLK1 cDNA by 16 amino-terminal residues. In contrast, hLGLK1 cDNA contains multiple initiator codons upstream of the predicted initiator codon at position 294 within the cassette exon. Translation of the two mRNAs in vitro by a reticulocyte lysate system resulted in proteins of the expected size (52 kDa) for both mRNAs; yet hLGLK2 mRNA was translated four to six times more efficiently. These results suggested that the alternative splicing of a cassette exon in hLGLK1 resulted in an mRNA with an upstream initiator codon and reduced function. The relative biological activity of the two isoforms of human glucokinase and their possible developmental and/or metabolic regulation remain to be determined.